Oreocharis purpurata, a new species of Gesneriaceae from Hunan, China - Han, Meng-Qi; Pan, Bo; Zou, Ling-Li; Liu, Yan (Phytotaxa, 2017)
Oreocharis purpurata B.Pan, M.Q.Han & Yan Liu, a new species of Gesneriaceae from central Hunan, China, is described and illustrated here. It is morphologically similar to O. pinnatilobata. The major difference is the two glandular ridges glands on the ventral corolla throat, which may be associated with pollinator attractions.